If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 3 = -12 Reorder the terms: 3 + -2x = -12 Solving 3 + -2x = -12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2x = -12 + -3 Combine like terms: 3 + -3 = 0 0 + -2x = -12 + -3 -2x = -12 + -3 Combine like terms: -12 + -3 = -15 -2x = -15 Divide each side by '-2'. x = 7.5 Simplifying x = 7.5
| 5(-2)-3b=15 | | 5(-4)-3b=15 | | -3x+2=8x+11-5x | | -10k-k=3(2k-12)-11(2k-4) | | 2b+b-6=0 | | 4(0)+8=6y | | n+20=25 | | 4(2)+8=6y | | 9x-22=68 | | 4(4)+8=6y | | -6x-16=-13-x | | x^3-7x^2-12x=0 | | 9x-22=6x | | 4(-2)+8=6y | | -4h-13=-17h-2h | | 13+8y=5 | | x^2+21x-40=0 | | -10(2x+12)=-8(x-9) | | -4x-.333=19.666 | | 2x^2+21x-40=0 | | 4(-4)+8=6y | | 4(2c+8)=5c+4 | | 6(0)-3y=18 | | 11n=10n+29 | | x*9-7= | | 4b+1=39 | | 6(2)-3y=18 | | 6(4)-3y=18 | | 2p^2-2p-14=0 | | 6(-2)-3y=18 | | 34x+100y= | | 34x-36y= |